German export performance - Sven W. Arndt (Intereconomics, 1983)
The Federal Republic of Germany's exports in 1980 represented approximately 23% of GNP. Germany's share of total world exports, however, declined throughout the seventies. What are the factors influencing German export performance? What is the outlook for the future?
Keywords: 330; External Trade